Melox (meloxicam) clinical efficacy in chronic joint diseases - Sh Erdes; E A Galushko; T N Tsapina (Научно-практическая ревматология, 2003)
Objective. To study efficacy and safety of Iwo doses of melox (meloxicam) in pts with rheumatoid arthritis (RA) and osteoarthritis (OA). Material and methods. An open uncontrolled study of melox was performed on 20 pts with chronic rheumatic diseases: 10 with RA and 10 with OA, 18 female and 2 male, mean age respectively 57,5±11,1 and 65,0±7,6 years, mean duration of the disease - 11,1 ±9,9 and 5,6±6,2 years. 90% of RA pis had 2nd activity degree and 1I-IV stage of the disease. 6 pts of OA group had gonarthritis and 4 - coxarthri- tis, 7 pts had 11 and 3 - 111 radiological stage according to Kellgren classification. The drug was administered orally during 4 weeks. Initial dose was 7,5 mg/day. In case of insufficient efficacy it was increased till 15 mg/day in 5 days. Results. All 20 pts completed 4-weeks study. There were no adverse events leading to withdrawal of melox. In 10 pts dose was increased from 7,5 to 15 mg/day - 2 with OA and 8 with RA. According to opinion of pts and investigators efficacy and tolerability were good or fair in 100%. Conclusion. The results of the study confirm that selective COX-2 inhibitors such as melox are effective, have good safety and usually do not cause serious adverse effects.